Eldecalcitol reduces osteoporotic fractures by unique mechanisms. Issue 148 (April 2015) - Kondo, Satoshi; Takano, Toshiyuki; Ono, Yoshiyuki; Saito, Hitoshi; Matsumoto, Toshio
Highlights: The 3-hydroxypropyloxy group (3-HP group) of eldecalcitol offers stronger binding to DBP and VDR. The 3-HP group of eldecalcitol interferes with its binding to CYP24A1. Eldecalcitol slightly increases the risk of hypercalcemia in CKD stage 3B patients. Eldecalcitol treatment does not cause sustained reduction in renal function. Abstract: Eldecalcitol shows higher binding affinity for vitamin D-binding protein (DBP), tighter binding to vitamin D receptor (VDR), and resistance to metabolic degradation via 24-hydroxylation. In silico analysis of the mode of binding demonstrated that the 3-hydroxypropyloxy (3-HP) group of eldecalcitol offers additional hydrogen bond and CH–π interaction for the binding to DBP and VDR. However, the 3-HP group interferes with the binding of eldecalcitol to CYP24A1, causing poor metabolic clearance of eldecalcitol by this enzyme. These characteristics may contribute to the stronger effect of eldecalcitol than calcitriol. The present post-hoc analysis also demonstrate that the incidence of hypercalcemia and hypercalciuria is slightly higher in eldecalcitol than in alfacalcidol group especially in patients with CKD stage 3B, that both serum and urinary calcium return to the baseline levels shortly after cessation of the treatment in both treatment groups, that the incidence of urolithiasis is higher in patients with higher eGFR and is similar between alfacalcidol and eldecalcitol groups, and that eGFR is transiently reduced by both alfacalcidol and eldecalcitol treatment especially among patients with higher eGFR but recovers after the end of both treatment. Eldecalcitol can be used for the treatment of osteoporosis without Ca supplementation to reduce the incidence of hypercalcemia and hypercalciuria, and enough hydration is recommended in order to avoid hypercalcemia, urolithiasis and deterioration of renal function.